Penile agenesis associated with anorectal malformation and bilateral renal agenesis: A case report and a review of the literature - Collins Chijioke Adumah; Iniofon Clement Akpaette; Owolabi Oni; Igwe Arua Obasi; Ibukunolu Olufemi Ogundele; Abdulhafiz Adesunkanmi; Oluwaseun Abioye Oyinloye; Ademola Olusegun Talabi; Oludayo Adedapo Sowande; Olusanya Adejuyigbe (African Journal of Paediatric Surgery, 2024)
Penile agenesis is complete absence of the penis in an otherwise normal phenotypic and genotypic male at birth that results from failure of development of the genital tubercle. It is an extremely rare anomaly that may be associated with anomalies in other organ systems, the extent and severity of which may affect the prognosis. The management is challenging and may have far reaching implications for the individual and family. While gender reassignment with bilateral orchidectomy and feminising genitoplasty has been carried out for most patients, significant psychosexual and social issues related to the male identity may occur due to foetal or postnatal sex steroid imprinting. We report a neonate with penile agenesis with bilateral renal agenesis and anorectal malformation.